Better Governance for Development in the Middle East and North Africa : Enhancing Inclusiveness and Accountability - World Bank (Washington, DC, 2013)
Development is often defined in terms of its economic aspects, as increased material well-being through ensured employment and income for all who want it. But as knows anyone whose children go to schools of poor quality, have no clean water to drink, or face the threat of violence, development is also about having access to adequate social services. And development is ultimately about human development-the quality of material living, with wider choices and opportunities for people to realize their potential, plus the guarantee of those intangible qualities that characterize all more-developed societies: equality of treatment, freedom to choose, greater voice, and opportunities to participate in the process by which they are governed. Virtually all constitutions in the Middle East and North Africa (MENA) region enshrine those values of development, and public governance is one of the mechanisms through which the values are secured for the people. From getting a driver's license in Casablanca to voting in municipal elections in Beirut, public governance relationships in the MENA region, as elsewhere, manifest themselves in almost every situation in which individuals and groups interact with the government. The challenge for governments and people throughout the region is to expand the interactions that are smooth and productive and to minimize the ones that are frustrating and wasteful-in a move toward "good" governance. If public governance is the exercise of authority in the name of the people, good governance is exercising that authority in ways that respect the integrity, rights, and needs of everyone within the state.